2015
DOI: 10.1016/j.jad.2015.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and psychomotor effects of three months of escitalopram treatment in elderly patients with major depressive disorder

Abstract: Please be advised that this information was generated on 2018-05-09 and may be subject to change. Background: Psychomotor retardation (PR) is one of the core features in depression according to DSM V (1), but also aging in itself causes cognitive and psychomotor slowing. This is the first study investigating PR in relation to cognitive functioning and to the concomitant effect of depression and aging in a geriatric population ruling out contending effects of psychotropic medication. PSYCHIATRY ORIGINAL RESEARC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…One possibility is that the observed pro-cognitive effects of SSRIs are actually mediated by other (non-1A) 5-HT receptors ( Boulougouris et al, 2008 ; Furr et al, 2012 ; Imoto et al, 2015 ), and another is that improvements in cognition in patients treated with SSRIs is an epiphenomenon of improvements in mood ( Chepenik et al, 2007 ). It is also important to note that the evidence that SSRIs improve cognition is relatively weak ( Beheydt et al, 2015 ; Knorr, 2012 ; Knorr et al, 2011 ; Siepmann et al, 2003 ) and their modest ability to address cognitive symptoms in depression is considered one of their limitations ( Popovic et al, 2015 ).…”
Section: Psychological Functions Associated With Brain 5-htmentioning
confidence: 99%
“…One possibility is that the observed pro-cognitive effects of SSRIs are actually mediated by other (non-1A) 5-HT receptors ( Boulougouris et al, 2008 ; Furr et al, 2012 ; Imoto et al, 2015 ), and another is that improvements in cognition in patients treated with SSRIs is an epiphenomenon of improvements in mood ( Chepenik et al, 2007 ). It is also important to note that the evidence that SSRIs improve cognition is relatively weak ( Beheydt et al, 2015 ; Knorr, 2012 ; Knorr et al, 2011 ; Siepmann et al, 2003 ) and their modest ability to address cognitive symptoms in depression is considered one of their limitations ( Popovic et al, 2015 ).…”
Section: Psychological Functions Associated With Brain 5-htmentioning
confidence: 99%
“…Notably, a previous meta‐analysis has substantiated the moderately favorable impact of antidepressants, 40 particularly SSRIs, on executive function among individuals with depression. Nevertheless, a study involving patients diagnosed with LLD revealed that while the administration of escitalopram for a duration of 12 weeks significantly ameliorated the depressive symptoms, it did not yield a significant improvement in executive function 41 . Consequently, it was imperative to undertake further investigation into the influence of SSRIs on executive function in LLD patients through meticulously high quality placebo‐controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…The studies that were included in which SSRI treatment lasted 12 weeks or longer ( Barch et al, 2012 ; Beheydt et al, 2015 ; Bondareff et al, 2000 ; Brendel et al, 2018 ; Butters et al, 2000 , 2011 ; Carrière et al, 2017 ; Cassano et al, 2002 ; Choe et al, 2016 ; Del Ser et al, 2019 ; Devanand et al, 2003 ; Jorge et al, 2010 ; Leng et al, 2018 ; Lenze et al, 2020 ; Mokhber et al, 2014 ; Munro et al, 2004 , 2012 ; Newhouse et al, 2000 ; Oh et al, 2021 ; Pirker-Kees et al, 2019 ; Robinson et al, 2000 ; Rocca et al, 2005 ; Rozzini et al, 2010 ; Weintraub et al, 2010 ) were slightly more likely to find positive effects than studies reporting results of treatments of 4 weeks or shorter ( Deakin et al, 2004 ; Furlan et al, 2001 ; Kerr et al, 1992 ; Martin et al, 1989 ; O’Carroll et al, 1994 ; Savaskan et al, 2008 ) and less likely to find negative results. This could indicate that long-term SSRI use does not have a deleterious effect on brain functions related to memory.…”
Section: Discussionmentioning
confidence: 99%